Harnessing Omni-channel Marketing Strategy for Digital Transformation in Sri Lankan Women-led Micro, Small and Medium Enterprises - Dilogini, S.; Kajanthy, V. (University of Vavuniya, 2024)
This qualitative study addresses a gap in literature by exploring how omni-channel marketing impacts Women-led Micro, Small, and Medium Enterprises (WMSMEs) in Sri Lanka, facilitating their digital transformation. Aa largely overlooked area, WMSMEs face distinct challenges and opportunities in using omni-channel marketing to improve competitiveness and efficiency. Despite its importance, there is limited research on how Sri Lankan WMSMEs are managing this shift. This study aims to fill that gap, offering insights and recommendations to support their digital growth and inclusion. It investigates how these strategies help WMSMEs overcome barriers like limited access to modern marketing practices, promoting sustainable growth and economic development. The research design employs case studies of fifteen Sri Lankan WMSMEs leveraging platforms like Facebook, WhatsApp, YouTube, Instagram, and physical channels. Purposive sampling is used to select the enterprises, ensuring that those included have experience with omni-channel marketing strategies. Data are collected through in-depth interviews and analyzed thematically. Results indicate that omni-channel marketing provides WMSMEs with innovative, cost-effective methods to reach diverse audiences and enhance visibility. For example, WMSMEs utilize physical outlets for local engagement, Facebook for international outreach, YouTube for product showcases, and WhatsApp for personalized customer interactions, improving satisfaction and loyalty. The study underscores omni-channel marketing's overlooked role in transforming WMSMEs in Sri Lanka, emphasizing how these strategies help overcome marketing challenges, expand audience reach, and enhance engagement. The findings suggest omni-channel marketing can bridge gender gaps in entrepreneurship, promoting economic empowerment for women entrepreneurs.
Keywords: Digital transformation; Omni-channel marketing strategies; Sri Lanka; Women-led micro small medium enterprises